„Jeruszalaim de Lite”. Obraz Wilna w opowiadaniu Grigorija Kanowicza Sen o Jeruzalem, którego już nie ma - Lenart, Agnieszka (Acta Polono-Ruthenica, 2018)
The considerations made in the article concern the image of Vilnius in the prose of Grigory Kanovich, a writer, who in all his previous works remains faithful to the Jewish Lithuania, which he remembers from his childhood. The story of Kanovich entitled Dream of Jerusalem, which no longer exists has been carefully analyzed. The post-war Jerusalem of North is undoubtedly the center of the Jewish ethnos, a mythical place, unique, admirable, but also a place of disappoint- ments, broken dreams, a city full of shed tears and marked by bloody events of the war. The theme of dream present in the work is at the same time longing for freedom, return to the ideal past, but also a symbol of fear and memory of the place which will never be the same again.